2010
DOI: 10.1590/s1517-83822010000400034
|View full text |Cite
|
Sign up to set email alerts
|

Production of extracellular lipases by Rhizopus oligosporus in a stirred fermentor

Abstract: The present investigation deals with the kinetics of submerged extracellular lipases fermentation by both wild and mutant strains of Rhizopus oligosporus var. microsporus in a laboratory scale stirred fermentor.Other parameters studied were inoculum size, pH, agitation and rate of aeration. It was found that the growth and lipases production was increased gradually and reached its maximum 9.07± 0.42 a U mL -1 (W) and 42.49 ± 3.91 a U mL -1 (M) after 30h of fermentation for both wild and mutant strain. There is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
(11 reference statements)
5
10
0
1
Order By: Relevance
“…Therefore, in this study, numbers of basic fermentation kinetics parameters were evaluated for developing a triumphant process which will be reasonably viable. As compared to the present study, similar type of observation was also reported by Iftikhar et al (2010) for production of lipase from Rhizopus oligosporus var. microsporus .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, in this study, numbers of basic fermentation kinetics parameters were evaluated for developing a triumphant process which will be reasonably viable. As compared to the present study, similar type of observation was also reported by Iftikhar et al (2010) for production of lipase from Rhizopus oligosporus var. microsporus .…”
Section: Discussionsupporting
confidence: 92%
“…But, the growth-independent coefficient of enzyme production (β) was optimum when fermentation was carried out by A. terreus using wheat bran as the substrate. Similar type of result was also proposed by Iftikhar et al (2010) for the biosynthesis of lipase from Rhizopusoligosporus var. microsporus.…”
Section: Batch Numbersupporting
confidence: 86%
“…Also, the ratio between the total unsaturated and saturated fatty acids was higher in the TNR and TNBR samples. The fungus R. oligosporus is well known for its ability to produce the lipase enzymes (ul-Haq et al 2002;Iftikhar et al 2010). It is therefore obvious that a significant shift in fatty acid contents found in the fermented soybean products was due to effect of fungal lipase enzymes.…”
Section: Resultsmentioning
confidence: 99%